2023
DOI: 10.1186/s12879-023-08413-7
|View full text |Cite
|
Sign up to set email alerts
|

Insight into pathogenomics and phylogeography of hypervirulent and highly-lethal Mycobacterium tuberculosis strain cluster

Abstract: Background . The Mycobacterium tuberculosis Beijing genotype is globally spread lineage with important medical properties that however vary among its subtypes. M. tuberculosis Beijing 14717-15-cluster was recently discovered as both multidrug-resistant, hypervirulent, and highly-lethal strain circulating in the Far Eastern region of Russia. Here, we aimed to analyze its pathogenomic features and phylogeographic pattern. Results . The study collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…L2.1 strains do not exhibit distinct clinically significant features and are characterized by moderate transmission capacity, as is the case in Japan (Guyeux et al, 2022). However, a study by Mokrousov et al found two clusters of the ancient Beijing sublineage in the Russian part of Asia, and, importantly, these strains were multidrug-resistant (Mokrousov et al, 2019(Mokrousov et al, , 2023. In contrast, modern sublineages of the Beijing family show a global distribution in various regions of the world (Figure 4).…”
Section: Geographic Distributionmentioning
confidence: 98%
“…L2.1 strains do not exhibit distinct clinically significant features and are characterized by moderate transmission capacity, as is the case in Japan (Guyeux et al, 2022). However, a study by Mokrousov et al found two clusters of the ancient Beijing sublineage in the Russian part of Asia, and, importantly, these strains were multidrug-resistant (Mokrousov et al, 2019(Mokrousov et al, , 2023. In contrast, modern sublineages of the Beijing family show a global distribution in various regions of the world (Figure 4).…”
Section: Geographic Distributionmentioning
confidence: 98%